(3JHjGf eTcd GdBKGQs - (3GdWMGhj , CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3jHOC HHGH eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ai GTO GdfGS YPGHkG jhe GdbjGeI s
(3BNQgG (B:s
(3jfJgi HCKfGA HGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ai GSe GdUdGI GdJGdjI dUdGI GdeZQH ef GdUdhGJ GdNeS s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs